KREATIVITAS YOLANDA PUTRI PROBOSEKAR DALAM KARYA TARI LEDHEK DI SANGGAR GUNTUR KOTA KEDIRI - Pramesti, Rory Nur; Slamet, Slamet (Greget: Jurnal Kreativitas dan Studi Tari, 2022)
This research was conducted as a study of the creativity of creating a new work inspired by Tayub folk art. Ledhek dance is a new creative dance of the folk tradition created by Yolanda Putri Probosekar and performed in 2019 at TMII. The problems in this study are first, how is the form of Yolanda Putri Probosekar's Ledek dance and second, how is Yolanda Putri Probosekar's creativity in creating the Ledhek dance. Answering the problem of dance form, the theory of Y. Sumandiyo Hadi is used regarding the elements of group choreography. Meanwhile, to find out the creativity of Yolanda Putri Probosekar, it is explained using the theory using the 4P (Four P's Creativity) theory from Rodhes which includes person, process, product, and press. This study uses a qualitative research method. The data collection techniques used are observation, interviews, and literature studies. This study describes the object of research according to the data in the field in the form of real data. The results of the study obtained are that Yolanda Putri Probosekar's creativity in creating the Ledhek dance is influenced by factors such as experience as a dancer and choreographer. This creativity is manifested in several developments of Tayub dance movements such as lembehan, ukel penthangan, ukel lembehan, and jogetan. Then presented with gamelan music, such as kendang, bonang barong, bonang penyerangabbta, peking, slentem, kempul, kenong, rebab, and gong.